Transarterial chemoembolization plus lenvatinib with or without programmed death-1 inhibitors for patients with unresectable hepatocellular carcinoma: A propensity score matching study - Guo, Peng; Pi, Xingtao; Gao, Feng; Li, Qiang; Li, Duqiang; Feng, Wendong; Cao, Wendong (Frontiers in Oncology, 2022)
Purpose We conducted a retrospective study to compare transarterial chemoembolization (TACE) plus lenvatinib plus programmed death-1 (PD-1) inhibitors with TACE plus lenvatinib in patients with unresectable hepatocellular carcinoma (HCC). Patients and methods Patients with HCC were analyzed from January 2018 to January 2022 in three hospitals. Patients received TACE plus lenvatinib with or without PD-1 inhibitors (TACE+L+PD-1 or TACE+L, respectively). The baseline characteristics of the two groups were compared, and propensity score matching (PSM) was performed. Overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) of the two groups were compared. Adverse events in the two groups were analyzed. Results A total of 166 patients were evaluated (TACE+L+PD-1, n = 75; TACE+L, n = 91). Before PSM, OS was prolonged in the TACE+L+PD-1 group (p = 0.010), but PFS was similar between the two groups (p = 0.18). ORR was higher in the TACE+L+PD-1 group (p = 0.047). After PSM, estimated OS rates at 6, 12, and 24 months were 97.9%, 84.6%, and 74.1%, respectively, in the TACE+L+PD-1 group (n = 48) and 93.1%, 66.1%, and 43.4%, respectively, in the TACE+L group (n = 48). Estimated PFS rates at 3, 6, and 12 months were 81.9%, 61.8%, and 30.9%, respectively, in the TACE+L group and 95.7%, 82.1%, and 68.4%, respectively, in the TACE+L+PD-1 group. OS, PFS, and ORR were improved in the TACE+L+PD-1 group compared to the TACE+L group (p = 0.030; p = 0.027; p = 0.013). The safety of the TACE+L+PD-1 regimen was acceptable. Conclusions The addition of PD-1 inhibitors to TACE+L significantly improved clinical outcomes in patients with unresectable HCC. Side effects were manageable.